42‐2: Establishment and Simulation Optimization of Optical Fingerprint Recognition Structure in LCD Screen. Issue 1 (25th September 2020) - Huang, Jianmou; Wang, Hailiang; Lin, Yan; Zhou, Wenqi; Long, Yaqiong; Yang, Yan; Wu, Ling; Zhou, Ting; Shen, Boping; Li, Junyi
Abstract : This paper reports a new type of liquid crystal screen which has an in‐screen optical fingerprint recognition collimation structure. The collimator structure in the TFT&CF glass in the screen has different opening size and height. Through simulation, the SNR( Signal to Noise Ratio )&CR(contrast ratio) evaluation criteria were obtained to judge the fingerprint identification accuracy of the collimating structure .Compared with the unoptimized structure, the optimized collimation layer improves the accuracy of fingerprint identification.